An Analysis of Student Difficulties in Solving the Word Problem. (October 2019) - Habibullah,; Hartono,
Abstract: This research is a qualitative descriptive research that aims to describe the types and factors of difficulty in solving mathematics problems in the form of word problems. The research subjects were 22 students who were selected by random sampling technique from one of the junior high schools in Indragiri Hilir. The data was collected through diagnostic tests and interviews conducted openly but not structured. In analyzing the students' difficulties, the revised Bloom's Taxonomy theory was used to find the difficulties in factual, conceptual, procedural, and metacognitive knowledge. The results of research showed that 14.77% of students had difficulties in factual knowledge, 17.05% of students had difficulties in conceptual knowledge, 45.46% of students had difficulties in procedural knowledge, and 53.41% of students had difficulties in metacognitive knowledge. The factors that cause difficulties were experienced by students, such as: their sense in lack of time, carelessness, anxiety, giving up easily, and being hasty in doing the given problem.